DAMPAK PENETAPAN TARGET PENERIMAAN PAJAKBUMI DAN BANGUNAN SEKTOR PERDESAAN DAN PERKOTAAN (PBBP2) TERHADAP PENERIMAAN PAJAK DAERAH KABUPATEN MUSI BANYUASIN - Farida Aryani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2019)
This research is intended to know the impact of PBBP2 acceptance to the regional tax. This research uses primary data from the results of interview with the collecting division of PBBP2, meanwhile the secondary data are report target and the realization of PBBP2 acceptance and regional tax of BPPRD of Muba 2014 to 2018. Technique of data analysis used is quantitative descriptive analysis technique by calculating target ratio and realization of PBBP2 acceptance, regional tax and graphic data presentation. The result of this research shows that the performance of BPPRD Muba in collecting regional taxes, especially PBBP2 is not optimum since the decision of PBBP2 acceptance target is not based on SPOP and is not appropriate with the tax potentiality, so PBBP2 target is not accurate. This gives the impact of low acceptance of regional tax from PBBP2 22.44%, so the regional tax acceptance from PBBP2 is relatively small, the average is only 15.07%. Thus, the realization of PBBP2 is very low during 2014 to 2018 only 64%. This is caused by the system and procedures of tax objects data collection are not accurate, the payment system is not online and just through the regional bank, lack of socialization and low awareness of tax obedience.